2021
DOI: 10.1111/1745-9133.12556
|View full text |Cite
|
Sign up to set email alerts
|

Elevated police turnover following the summer of George Floyd protests: A synthetic control study

Abstract: Research summary Several of the largest U.S. police departments reported a sharp increase in officer resignations following massive public protests directed at policing in the summer of 2020. Yet, to date, no study has rigorously assessed the impact of the George Floyd protests on police resignations. We fill this void using 60 months of employment data from a large police department in the western United States. Bayesian structural time‐series modeling shows that voluntary resignations increased by 279% relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 83 publications
1
54
0
Order By: Relevance
“…Police officers have long been considered to have a “cover your ass” mentality to ensure continued employment (Van Maanen, 1978), and heightened national attention to police behavior and police reform have likely enhanced this orientation among officers who are feeling immense scrutiny due to what some have called a legitimacy crisis in policing (Todak, 2017). For instance, recent research has identified high rates of police turnover following protests related to the death of George Floyd in Minneapolis, Minnesota, a fatal police use of force incident captured using a BWC (Mourtgos et al., 2021). As such, a combination of current sentiment toward the police and additional scrutiny facilitated by BWCs could change the way officers behave.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Police officers have long been considered to have a “cover your ass” mentality to ensure continued employment (Van Maanen, 1978), and heightened national attention to police behavior and police reform have likely enhanced this orientation among officers who are feeling immense scrutiny due to what some have called a legitimacy crisis in policing (Todak, 2017). For instance, recent research has identified high rates of police turnover following protests related to the death of George Floyd in Minneapolis, Minnesota, a fatal police use of force incident captured using a BWC (Mourtgos et al., 2021). As such, a combination of current sentiment toward the police and additional scrutiny facilitated by BWCs could change the way officers behave.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several scholars provide evidence that higher informational justice perceptions among public sector employees is associated with lower turnover intentions and greater job satisfaction (H.-S. Kim, 2008;Moon, 2017). The last decade has seen law enforcement agencies experiencing a recruitment and retention crisis (Mourtgos et al, 2021;J. M. Wilson et al, 2010), and so any ways to combat turnover is of salience to practitioners.…”
Section: Fairness Outcomesmentioning
confidence: 99%
“…A final area of interest to law enforcement practitioners and scholars alike is the relationship between organizational justice and low morale, "de-policing," and similar concepts speaking to whether modern officers are retreating from extremes of negative public sentiment by pulling-back from "normal" police activity (Mourtgos & Adams, 2019;Mourtgos et al, 2021;Phillips, 2020a;Pyrooz et al, 2016). A survey of deputy sheriffs in the post-Ferguson era (n=510) found that many officers were less motivated to continue working in law enforcement, but that outcome was blunted in officers with higher perceptions of organizational justice (Nix & Wolfe, 2016).…”
Section: Fairness Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early research showed that officers were particularly concerned with exposing their loved ones to COVID-19 (Jennings and Perez, 2020). The pandemic converged with renewed calls for police reform and nationwide protests of police brutality and the combination of these factors are, at least, moderately responsible for the large-scale workforce reduction experienced by many police departments, especially in large, urban jurisdictions (Mourtgos et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%